(untitled) (Revista Electrónica Calidad en la Educación Superior, 2024)
Mobile learning aligns with the current trends in distance education, incorporating the use of mobile devices, including smartphones. The objective of this article is to analyze the mobile learning model in relation to competencies and teaching strategies grounded in the use of technology and levels of virtualization. The study was conducted through a systematic literature review of 32 sources of information to clarify concepts and references related to the topic, ensuring credibility and reliability of sources. The conclusions highlight the importance for both educators and students to develop technological competencies, with educators focusing on integrating devices into teaching with appropriate methodologies, while students adapt to the use of mobile devices and emerging trends.